Retrospective analysis of outcome and toxicity after postoperative radiotherapy in patients with squamous cell carcinoma of the lip. Issue 2 (April 2022) - Lang, Kristin; Akbaba, Sati; Held, Thomas; El Shafie, Rami; Farnia, Benjamin; Bougatf, Nina; Bernhardt, Denise; Freudlsperger, Christian; Plinkert, Peter K.; Rieken, Stefan; Debus, Jürgen; Adeberg, Sebastian
Background: Carcinomas of the lips are a relatively common malignancy of the head and neck region, accounting for roughly one quarter of all oral cavity cancers. Compared to other oral cancer sites, this location has a favorable prognosis, with 5-year survival rates between 85% and 95%. This study summarizes our institutional experience in utilizing postoperative radiation for patients with squamous cell carcinoma of the upper and/or lower lip following incomplete surgical resection or positive lymph node involvement with extracapsular extension. Methods: We retrospectively reviewed the medical records of all patients at the University Hospital of Heidelberg between 2005 and 2018 treated with postoperative radiotherapy of the upper and lower lip. Nineteen patients were identified with a median age at diagnosis of 67 years (range, 41–95 years), with 58% male and 42% female patients. Fourteen patients (73.7%) underwent neck dissection, with 5 (35.7%) found to have extracapsular extension (ECE) and positive resection margin (R1/2), 2 (14.3%) only ECE, and 7 (50.0%) with only R1/2. All patients received a median cumulative dose of 66.0 Gy (range, 60.0–70.0 Gy) in a median of 2.0 Gy per fraction (range, 1.8–2.2 Gy). Results: Median follow-up was 5.2 years. The median progression-free survival (PFS) was 3.9 years (range, 0.2–12.4 years), local disease-free survival (LDFS) was 4 years (range, 1–12 years) and overall survival (OS) was 5.2 years (range, 0.2–12.4 years). The 5-year Kaplan-Meier estimates for OS, PFS, and LDFS were 61.4%, 85.7%, and 100.0%, respectively. At last follow-up, 13 patients (68.4%) were still alive. Although no patient developed locoregional relapse, two patients developed distant relapse at a median of 15 months after radiotherapy. There was a statistically significant improvement in OS in patients treated with higher radiotherapy doses (>60.0 Gy, p = 0.044) compared to lower radiotherapy doses. PFS was significantly improved among patients who had N0 disease, with a negative resection margin, without ECE, and who were treated with intensity-modulated radiotherapy to doses >60.0 Gy. No grade 3/4 toxicity was detected; the most common grade 1/2 toxicities included dermatitis (n = 11, 57.9%), oral mucositis (n = 8, 42.1%), and dysphagia (n = 8, 42.1%). Conclusion: Our results demonstrate excellent local control and OS with acceptable toxicity when utilizing postoperative radiotherapy in patients with squamous cell carcinoma of the upper and lower lip, despite unfavorable characteristics (advanced T or N stage and/or ECE).